Evaluating the outcomes of a hearing screening service for grade one learners in urban areas at Durban, South Africa - Samantha Govender (Journal of Public Health in Africa, 2015)
Early intervention through hearing screening can reduce the negative impact of hearing loss for children. Optimal outcomes are achieved when an appropriate screening protocol is selected, a pathway for follow up care is established, and when a hearing conservation component is included. This study aimed to describe the outcomes of a hearing screening service provided to grade one learners in urban areas at Durban. A cross-sectional design was employed. Learners (n=241) were conveniently sampled from six randomly selected schools. They were screened using otoscopy, tympanometry and pure tone audiometry. Fifty eight participants (24%) obtained a refer result, with 33% referred for diagnostic assessments, 29% for middle ear pathology and 38% for cerumen management. Findings further revealed that only 33% of referrals were followed up indicating poor compliance. Association between test results and income levels (P=0.38) as well as distance to the nearest health care facility (P=0.22) did not influence test outcomes. School aged children do present with common ear problems. Appropriate protocol selection, ensuring compliance to recommendations and education on hearing conservation are essential components of any health initiative.